Asset Mapping as a Base for Traditional Islamic Boarding School (Pesantren) Sheep Farming Development in Ngawonggo Village, Malang Regency, Indonesia - Azizah, Siti; Ningsih, Umi Wisapti; Djunaidi, Irfan H (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The research aim was to identify the assets of Ngawonngo Village, Malang Regency to support the establishment of Traditional Islamic Boarding School Sheep Farming. The study was conducted in Ngawonggo Village, Tajinan District, Malang Regency. The methods used in the research was qualitative research with descriptive data analysis. The results of the study There are six (physical, natural resources, human resources, financial, technology, and social capital) of Ngawonggo Village, Tajinan District, Malang Regency. Lack of physical, technological, and financial assets has a positive side where people will have a stronger motivation to improve their wellbeing. The potential of natural assets, human resources, and social capital can solve community problems and improve other assets that are not yet optimal. The sheep breeding business initiated by the pesantren as an influential institution is a strategic plan to develop the Tajinan Village as a center for sheep farming.